Under Pressure Benchmark for DDBMS Availability - Fior, Alessandro Gustavo; Meira, Jorge Augusto; Almeida, Eduardo Cunha de; Coelho, Ricardo Gonçalves; Del Fabro, Marcos Didonet; Le Traon, Yves (Journal of Information and Data Management, 2013)
The availability of Distributed Database Management Systems (DDBMS) is related to the probability of being up and running at a given point in time and to the management of failures. One well-known and widely used mechanism to ensure availability is replication, which includes performance impact on maintaining data replicas across the DDBMS's machine nodes. Benchmarking can be used to measure such impact. In this article, we present a benchmark that evaluates the performance of DDBMS, considering availability through replication, called Under Pres- sure Benchmark (UPB). The UPB measures performance with di?erent degrees of replication upon a high-throughput distributed workload, combined with failures. The UPB methodology increases the evaluation complexity from a sta- ble system scenario to a complex one with di?erent load sizes and replicas. We validate our benchmark with three high-throughput in-memory DDBMS: VoltDB, NuoDB and Dbms-X.